Mondialisation et nouvelle mobilité des élites africaines - Michel Lesourd (EchoGéo)
Today, the social class of “leaders” in Africa (high public official, political elite, business managers, big traders) is the main benefiter of the wealth accumulation process that has been created by the globalization, the development of exchanges and communication, as well as the global economic deregulation. Since the 2000’s, some capital holders investments and local touristic policies have significantly increased land speculation and real estate growth in several “South” cities such as Dakar, Marrakesh, Luanda or Praia. In spite of increasing social inequalities in the economic context marked by structural adjustment since the 1980s, an African elite has raised on the basis of entrepreneurship either formal or informal. Their financial capacities and their social influence allowed them to achieve this accumulation process. This new African elite class cannot be compared to the Indian middle-upper consumption class but is nevertheless aspiring for the western consumption standards.These “nouveaux riches” take part in the global nomadic world but the observation of their behaviour shows that these “new nomads” are actually combining different kinds of mobility, for different purposes such as traditional commitments, social relationships, business, leisure, and consumption. Several effects of this phenomenon can be observed. In the big cities, the new bourgeoisie migrates to living districts, contributing to the intensification of urban social division. The traditional and social commitments (due to the funerals, the celebrations, etc.) remain a major purpose of local, national or international mobility and the religious purpose (especially for pilgrimage) has been significantly increasing. Two new behaviours can be identified. The first is the leisure trip of the weekends, generally in the local area with all the family. The second one is the trip combining different purposes: social visit or tourism during a professional trip, commercial operation combined to a family visit, etc. This kind of journey is particularly frequent in the societies that have a tradition of international emigration like Senegalese and Cap Verdean societies.The contribution of African elites to the nomadic planet is thus complex, because it combines the local place with the world movements, the pleasant to the useful, and the duty in the leisure. Is it a new model of circulation in a world and an original contribution to the globalisation? We shall lean more specifically on Senegalese, Cape Verdean, Moroccan examples.